2010
DOI: 10.1159/000313282
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Sensorineural Hearing Loss and Normal Vestibular Function in a Dutch DFNB7/11 Family with a Novel Mutation in <i>TMC1</i>

Abstract: In a Dutch family with autosomal recessive hearing loss, genome-wide single-nucleotide polymorphism analysis mapped the genetic defect to the DFNB7/11 locus. A novel homozygous A-to-G change in the TMC1 gene was detected near the splice donor site of intron 19 (c.1763+3A→G) segregating with the hearing loss in this family. One of the 6 transmembrane domains and the actual TMC channel domain are predicted to be absent in the mutant protein. The sensorineural hearing impairment in this DFNB7/11 family has a post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 86 publications
2
26
0
Order By: Relevance
“…Consistent with the genetic data linking TMC1 and TMC2 to a role in hearing, it has been shown that Tmc1 and Tmc2 mRNA is expressed in the inner ear (12,17). Moreover, it has been suggested that the two genes may functionally compensate for each other in inner ear functions (21).…”
Section: Figuresupporting
confidence: 54%
“…Consistent with the genetic data linking TMC1 and TMC2 to a role in hearing, it has been shown that Tmc1 and Tmc2 mRNA is expressed in the inner ear (12,17). Moreover, it has been suggested that the two genes may functionally compensate for each other in inner ear functions (21).…”
Section: Figuresupporting
confidence: 54%
“…Tmc1 mRNA is expressed in auditory and vestibular hair cells (1,2), but there is no evidence of vestibular dysfunction associated with TMC1 or Tmc1 mutations (1,2,(6)(7)(8). Tmc2 mRNA is also detectable in mouse inner ear (1), but neither TMC2 nor Tmc2 has been implicated in inner ear dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Intra-or inter-familal phenotypic variability is also observed due to progression of hearing loss (DFNB7,DFNB8,DFNB25,DFNB30,DFNB59,DFNB72/95,DFNB77,DFNB79,DFNB84 and DFNB91) (Charizopoulou et al, 2011;de Heer et al, 2011;Ebermann et al, 2007b;Grillet et al, 2009;Li et al, 2010;Rehman et al, 2011;Schraders et al, 2010a;Schraders et al, 2010b;Sirmaci et al, 2010;Walsh et al, 2002;Weegerink et al, 2011). Younger individuals with mutations in BSND (DFNB73) also have a less severe degree of hearing loss which suggests a progressive nature of their hearing loss .…”
Section: Molecular Geneticsmentioning
confidence: 99%
“…However, a Dutch family with autosomal recessive hearing loss was reported in which affected individuals had a postlingual onset, progressive hearing loss due to a mutation near the donor splice site of intron 19 (c.1763+3A→G) in TMC1 (de Heer et al, 2011). The hearing loss initially affected the high frequencies and by second decade of life the hearing loss progressed to profound degree.…”
Section: Tmc1 (Dfnb7)mentioning
confidence: 99%
See 1 more Smart Citation